The Modern Census: Evolution, Examples and Evaluation1. (December 2013) - Baffour, Bernard; King, Thomas; Valente, Paolo
Summary A national census provides important information on a country's population that is used in government planning and to underpin the national statistical system. Therefore, the quality of such information is paramount but is not as simple as the crude accuracy of population totals. Furthermore, changes in the pace and nature of modern life, such as the growing geographical mobility of the population, increasingly pose challenges to census practice and data quality. More recently, even the need for a census has been questioned on grounds of financial austerity and widespread availability of alternative population information sources. This article reviews how the modern census originated and how it evolved to confront these challenges, driven by indicators of quality and needs of users, and provides reflections on the future of the census within the national statistical infrastructure. To illustrate our discussions, we use case studies from a diverse range of national contexts. We demonstrate the implications that a country's needs, circumstances and experiences have on the census approach and practice while identifying the fundamental demographic assumptions.